Urban Politics as the Unfolding of Social Relations in Place: The Case of Sexually Transmitted Disease Investigation in Mid‐Twentieth‐Century Gay Seattle. (12th March 2018) - Knopp, Larry; Brown, Michael; Mckeithen, Will
Abstract: Recent debates in urban politics stress the need to broaden conceptions of what counts as urban politics, as well as of where they take place. This means shifting attention to include more quotidian and prosaic social relations, including those taking place in spaces of civil society. We answer this call with a case study of the relations between an emerging gay male community in mid‐twentieth‐century Seattle, USA and the local public health department's disease investigators (DIs). We focus on both the biopolitics and cultural politics of the investigation process, from the perspectives of both DIs and gay men. We point out certain tensions and paradoxes in these processes as a form of governmentality, and interpret them through a 'noir' cultural lens that is consistent with a notion of urban politics as the unfolding of social relations in place. We conclude by stressing how our findings and framework can augment urban political inquiry both intellectually and empirically.